A New Medical Evaluation for Gastric Cancer Patients to Increase the Success Rate of Immunotherapy: A 2024 Update - Gabriel Samasca; Claudia Burz; Irena Pintea; Adriana Muntean; Diana Deleanu; Iulia Lupan; Vasile Bintintan (MDPI AG, 2024)
Researchers have performed numerous studies on immunotherapy because of the high death rate associated with gastric cancer (GC). GC immunotherapy research has made tremendous progress, and we wanted to provide an update on this topic. On the basis of this update, we suggest performing a new medical evaluation before initiating immunotherapy in patients with GC to increase the success rate of immunotherapies. We propose that before patients start GC immunotherapy, they should be evaluated and given a score of one to two points for the following factors: immunopathological features, molecular and genomic features, potential consequences for bacterial pathogens, potential immunotherapeutic resistance and hyperprogressive illness, and the potential to use biomarkers to gauge their prognosis and immunotherapy responses to optimize immunotherapy following surgery. The proposed scoring system could also help in the diagnosis of GC. With all the advances in genetics, immunology, and microbiology, the diagnosis of GC could be improved, not changed. Currently, patients diagnosed with GC undergo surgical resection as the only permanent solution. Patients who meet the maximum score from the presented proposal could be eligible immediately after diagnosis for immunotherapy. Therefore, immunotherapy could be a first-line option for clinicians.